2015
DOI: 10.1097/pcc.0000000000000446
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Critical Care Nursing Research Priorities—Initiating International Dialogue

Abstract: The consensus meeting was effective in organizing pediatric critical care nursing knowledge, identifying knowledge gaps and in prioritizing nursing research initiatives that could be used to advance nursing science across world regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 82 publications
1
11
0
2
Order By: Relevance
“…, ) and children's critical care nursing internationally (Tume et al . ). The alternative approach has been broader, identifying general, cross‐speciality priorities for children's nursing at a national level (Broome et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…, ) and children's critical care nursing internationally (Tume et al . ). The alternative approach has been broader, identifying general, cross‐speciality priorities for children's nursing at a national level (Broome et al .…”
Section: Introductionmentioning
confidence: 97%
“…Initiatives to involve nurses in setting research priorities vary widely in their focus, methodology, stakeholders and context. In child health, there have been numerous population-specific studies, for example, establishing research priorities for children's intensive care nursing in Australia and New Zealand (Ramelet et al 2011), children's cancer nursing at one tertiary hospital in Australia (Monterosso et al 2001), children's haematology and cancer care in the UK (Soanes et al , 2003 and children's critical care nursing internationally (Tume et al 2015). The alternative approach has been broader, identifying general, cross-speciality priorities for children's nursing at a national level (Broome et al 1996;Schmidt et al 1997;Brenner et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Italy, no rigorous instruments are available to evaluate parent satisfaction and experiences in NICU with FCC. Furthermore, considering that FCC was ranked as the second research priority domain in NICUs across Europe [ 12 ], and was identified as a priority in pediatric critical care research by international experts [ 13 ], a validated instrument to measure outcomes and benchmark parent satisfaction is needed.…”
Section: Introductionmentioning
confidence: 99%
“…(Henderson & Knapp, 2006). More recently, at the Seventh World Congress on Pediatric Intensive and Critical Care, one priority in the domain “Caring for patient’s families” was identified to evaluate the long-term psychosocial impact of a child’s critical illness on family outcomes (Tume et al, 2015). Parents’ experience during a child’s resuscitation may lead to long-term psychosocial impact on a family system.…”
Section: Discussionmentioning
confidence: 99%